Micron- and nanosized alloy particles made by electric explosion of W/Cu-Zn and W/Cu/Ni-Cr intertwined wires for 3D extrusion feedstock - Lerner, Marat I.; Suliz, Konstantin V.; Pervikov, Alexander V.; Tarasov, Sergey Yu (Materials)
A novel approach to electric explosion of intertwined wires to obtain homogeneous powder mixtures intended for preparing feedstock for extrusion 3D printing has been applied. The powder were composed of spherical micron- and nano-sized W/Cu particles in-situ alloyed by Zn and Ni during electric explosion of intertwined dissimilar metal wires is offered. The mean particle size measured by micron-sized particles was not more than 20 m. The average number size of these particles was 3 m and it was dependent on the energy input. The powders contained phases such as -W, -W/W3O as well as FCC -Cu(Zn) and -Cu(Ni) solid solutions with the crystalline lattice parameters 3.629 and 3.61 A, respectively